2019
DOI: 10.1111/jocn.14810
|View full text |Cite
|
Sign up to set email alerts
|

An educational intervention on foot self‐care behaviour among diabetic retinopathy patients with visual disability and their primary caregivers

Abstract: Aims and objectives To assess the effectiveness of a 12‐week educational intervention on foot self‐care behaviour among diabetic retinopathy patients with visual disability and their primary caregivers in China. Background Diabetes with the coexistence of diabetic retinopathy and foot problems complicating diabetes not only represents a personal disaster, but also becomes a serious burden to public health in China. A foot self‐care educational intervention is both cost‐effective and feasible even in a health r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 43 publications
0
41
0
1
Order By: Relevance
“…Since this was a cross‐sectional observational study, the causal relationship between self‐efficacy of foot care behaviour and diabetic microangiopathy was not clarified. However, studies have found that many patients with diabetes with retinopathy and neuropathy did not engage in foot self‐care behaviour 19,20 . From the present study, the reason may be associated with the lack of confidence in engaging in foot care behaviour due to visual impairment and sensory impairment of the skin.…”
Section: Discussionmentioning
confidence: 58%
“…Since this was a cross‐sectional observational study, the causal relationship between self‐efficacy of foot care behaviour and diabetic microangiopathy was not clarified. However, studies have found that many patients with diabetes with retinopathy and neuropathy did not engage in foot self‐care behaviour 19,20 . From the present study, the reason may be associated with the lack of confidence in engaging in foot care behaviour due to visual impairment and sensory impairment of the skin.…”
Section: Discussionmentioning
confidence: 58%
“…These seventeen studies included a total of 3149 patients and 36 healthcare professionals. Seven randomised controlled trials (RCTs), [51][52][53][54][55][56][57] four pre-test post-test design, [58][59][60][61] and others that included quasi-experimental studies, [62][63][64][65] studies within an RCT, 66 retrospective studies 67 and outcomes monitoring 46 were reported on.…”
Section: Resultsmentioning
confidence: 99%
“…Los resultados anteriores ratifican la importancia de brindar información desde los primeros niveles de atención en salud y por personal preparado que identifique a los pacientes con DM, así como la intervención que se necesita para mejorar este tipo de autocuidado de forma rutinaria (26,28,30,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). En definitiva, se necesita un mayor desarrollo de programas en este sentido, que además involucren la familia (60), a fin de que estas intervenciones educativas fomenten comportamientos positivos y efectivos de autocuidado (61).…”
Section: Categoría 4: Impacto De Las Intervenciones En El Nivel De Autocuidadounclassified